Abstraction framework to support students in learning creative conceptual design. Issue 4 (16th August 2018) - Fiorineschi, Lorenzo
Abstract : Purpose: Learning systematic conceptual design approaches could be difficult for students who are asked to adapt their intuitive design rationale to more abstract and divergent thinking styles. The purpose of this study is to propose a conceptual design approach with a well-defined reference framework and procedure to help students to gradually move toward concreteness and to explore the design space. Design/methodology/approach: The so-called problem–solution network approach has been taken as a reference and upgraded with a specific framework to manage abstraction levels. A first didactical application of the proposal is described, and specific feedbacks from students have been collected by means of an anonymous survey. Findings: Despite the limited course time allotted for the argument, students' feedbacks revealed that the proposed abstraction framework is useful to learn systematic conceptual design and to support the understanding of creative design thinking. Research limitations/implications: The proposal has been applied on a single class of MS engineering students in a course where only a part of the available time was allotted to conceptual design activities. However, the received positive feedbacks are encouraging and allow pushing toward more comprehensive applications and investigations. Originality/value: The proposal shown in this paper uses acknowledged concepts of abstraction and function to propose a new integrated framework to manage abstraction levels in problem solving activities. The framework has been implemented in a very recent conceptual design approach based on problem–solution co-evolution, which has been proposed to overcome the flaws ascribed to classical function-based methods.